Variáveis de projeto e sua influência no desempenho e dimensionamento de reservatórios de aproveitamento de água da chuva - Perius, Carla Fernanda (2016)
Rainwater harvesting (RWH) for non-potable use in buildings are a widespread practice around the world. The reservation is the item with the greatest variability in the RWH system design. The reservoir volume must be optimized in a way that it is not too large and costly, and not too small and insufficient to meet the demands. In this context, the objective of this work was to evaluate the influence of the project variables (faults in the rainfall series, catchment-demand conditions, initial reserve situation, discharge volumes, different demand series, changes in precipitation series) in the volume and performance of RWH tanks. For this, different catchment areas (100, 200 and 300 m²) were considered, located in five cities of Brazil - Porto Alegre, RS; Sao Paulo-SP; Goiânia, GO; João Pessoa, PB and Manaus, AM, thus contemplating different pluviometry regimes. For this purpose, the volume balance methodology was used, evaluating results for different commercial tanks volumes (1,000 L, 1,500 L, 2,000 L, 3,000 L and 5,000 L). Regarding the initial simulation criteria (catchment-demand conditions, initial reservation situation, discard volumes), the first discard runoff generated the most representative changes in the failure to meet the demand (8%). In relation to the different demand series, an increase of 40% in demand volume caused a 2.5-fold increase in the storage volume in regions with low rainfall seasonal variability and up to 5 times the size of the reservoir in the regions with well-defined seasonality. With regard to the different rearrangements of the series of precipitations, the inter-annual and intra-annual variations did not cause major changes in the failure of demand supply. Thus, based on the results found, it is recommended to consider the influence of the extension and the temporal discretization of the precipitations series in the rainwater reservoir design.